Hierarchy in adaptive radiation: A case study using the Carnivora (Mammalia). (1st February 2019) - Slater, Graham J.; Friscia, Anthony R.
Abstract: Simpson's "early burst" model of adaptive radiation was intended to explain the early proliferation of morphological and functional variation in diversifying clades. Yet, despite much empirical testing, questions remain regarding its frequency across the tree of life. Here, we evaluate the support for an early burst model of adaptive radiation in 14 ecomorphological traits plus body mass for the extant mammalian order Carnivora and its constituent families. We find strong support for early bursts of dental evolution, suggesting a classic Simpsonian adaptive radiation along dietary resource axes. However, the signal of this early burst is not consistently recovered in analyses at the family level, where support for a variety of different models emerges. Furthermore, we find no evidence for early burst–like dynamics in size–related traits, and Bayesian analyses of evolutionary correlations corroborate a decoupling of size and dental evolution, driven in part by dietary specialization. Our results are consistent with the perspective that trait diversification unfolds hierarchically, with early bursts restricted to traits associated with higher level niches, such as macrohabitat use or dietary strategy, and thus with the origins of higher taxa. The lack of support for early burst adaptive radiation in previous phylogenetic studies may be a consequence of focusing on low‐level niche traits (i.e., those associated with microhabitat use) in clades at shallow phylogenetic levels. A richer understanding of early burst adaptive radiation will require a renewed focus on functional traits and their evolution over higher level clades.